Identification of new reference genes with stable expression patterns for cell cycle experiments in human leukemia cell lines - Otília Tóth; Gergely Attila Rácz; Eszter Oláh; Máté Tóth; Edit Szabó; György Várady; Beáta G. Vértessy; Nikolett Nagy (Scientific Reports)
Abstract Cell cycle-dependent gene expression analysis is particularly important as numerous genes show tightly regulated expression patterns at different phases of the cell cycle. For cancer cells, analysis of cell cycle-related events is of paramount significance since tumorigenesis is characteristically coupled to cell cycle perturbations. RT-qPCR is a highly sensitive technique to investigate cell cycle-dependent transcriptional regulation. However, for reliable evaluation of qPCR data reference genes with stable mRNA expression are required. Although several studies investigating cell cycle-dependent gene expression employ frequently used reference genes, the suitability of these reference genes has not been thoroughly investigated so far. Moreover, such potential reference genes for cell cycle analysis have not been described in the literature. Therefore, we aimed to identify reference genes characterized with stable expression throughout the cell cycle in MOLT4 and U937 human leukemia cell lines synchronized with RO-3306 CDK1 inhibitor using RT-qPCR. Here we show that for cell cycle-dependent gene expression analysis the commonly used TBP is suitable, while the recently recognized reference genes SNW1 and CNOT4 are applicable in a cell line-dependent manner. We also suggest that proper selection of reference genes for each experimental condition is crucial for reliable normalization as these aspects can severely compromise conclusions.